New Genetics, New Identities - Atkinson, Paul; Glasner, Peter; Greenslade, Helen (Genetics and Society, 2007)
What implications are applications of new genetic technologies in biomedicine having on social identity in today's society? New Genetics, New Identities, a wide-ranging multi-disciplinary volume in the CESAGen Genetics & Society Book series, presents not only theoretical reflection but also empirical case studies drawn from an international array of authors. Including the highly controversial areas of reproductive technologies and use of human embryos in biomedical research, other key features include: a fresh analysis of a wide-range of social and political concerns in the development of new social identities examinations of the social implications of identity formation as a result from advances in genetic technologies from a number of perspectives both locally and globally resources of a wide range of social science disciplines to discuss significant sociological, anthropological, political and ethical issues. This superb collection is an essential informative read for postgraduates and academics in the fields of sociology, anthropology and scientific technologies giving a comparative approach to complex issues surrounding the social implications of these advances in a period of rapid social change.